Предмет: Алгебра,
автор: galinasabirova
Помогите упростить выражение спасибо
(x/(xy+y^2 )-y/(x^2+xy))*( x/(x^2-y^2 )-1/(x+y))
Ответы
Автор ответа:
0
(х/(у(х+у))-у/(х(х+у)))*(х/((х+у)(х-у))-1/(х+у))=
((х^2-у^2)/(ху(х+у)))*((х-1*(х-у))/((х+у)(х-у)))=
(((х-у)(х+у))/(ху(х+у)))*((х-х+у)/((х+у)(х-у)))=
((х-у)/ху)*(у/((х+у)(х-у)))= 1/(х(х+у)).
((х^2-у^2)/(ху(х+у)))*((х-1*(х-у))/((х+у)(х-у)))=
(((х-у)(х+у))/(ху(х+у)))*((х-х+у)/((х+у)(х-у)))=
((х-у)/ху)*(у/((х+у)(х-у)))= 1/(х(х+у)).
Похожие вопросы
Предмет: Қазақ тiлi,
автор: madiarmejirzanly
Предмет: Математика,
автор: ksenia56784
Предмет: Қазақ тiлi,
автор: alisherzhanybek
Предмет: Биология,
автор: Аноним
Предмет: Обществознание,
автор: andutkin